Scholastic Meditations - Rescher, Nicholas (Book collections on Project MUSE., 2005)
"The studies gathered in this volume seek to do homage to the spirit of Scholasticism. They address key issues in that tradition - some from a historical point of view, others from a more substantive standpoint."--Jacket